Hydrodynamic ram analysis in high-speed projectile penetrating into water-filled vessels. (1st May 2022) - Guo, Zitao; Chen, Tuo; Zhao, Geng; Zhang, Wei
Abstract: Hydrodynamic ram (HRAM) is a phenomenon that occurs when a high-speed projectile penetrates a fluid-filled tank, where the energy transferred to the liquid could result in a catastrophic failure and excessive structural damage. It is essential to take physical comprehension of the hydrodynamic effects that occur during an HRAM event in the civilian domain as well as for the military aircraft design, which would in fact contribute to design better structures with respect to this particular threat. For this present work, the HRAM due to cavity evolution in confined vessels under ballistic impact by projectiles was investigated through theoretical analysis combined with experimental results. Taking the confinement effects due to the limited size of the fluid-filled vessel and corresponding structure deformation into account, a model is proposed to describe the pressure between the liquid and vessel wall along the penetration trajectory based on cavity dynamics analysis. By studying relevant parameters, changes of wall pressure, non-dimensional disturbance range and energy of two extreme containers, (namely, non-pressure resistance containers and rigid containers without deformation) were examined. The results show that the cavitation pressure has less intense peak but much greater temporal extent compared with the pressure generated during the shock stage, thereby the cavity pressure impulse induced by cavity evolution is a non-negligible factor affecting the deformation and failure of a fluid-filled vessel. The aim of the present work is to reveal the mechanism of the pressure acting on the container wall caused by cavity evolution rather than the initial shock wave in an HRAM event, which will help to study the nature of hydrodynamic ram and understand the role of the cavitation pressure in the damage or deformation of liquid-filled vessels under projectile impact. Highlights: Considering the vessel deformation, an energy conservation equation is built. A model is proposed to describe the wall pressure induced by cavity evolution. The cavitation pressure distribution along the penetration trajectory is studied. Energy distribution along the penetration trajectory is studied. Vessel size confinement effect on cavity evolution is analyzed.